2014
DOI: 10.1080/08964289.2013.833083
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Predictors of Quality of Life in Hematological Cancer

Abstract: The improvement of health related Quality of Life (QOL) has become one of the main objectives of psychological interventions in cancer. The aim of this study was to analyze sociodemographic and psychosocial variables that predict the different components of QOL in a sample of 69 hemato-oncological patients. Depression, social support, disease-related stress situations, coping strategies and optimism were taken as psychosocial predictors. QOL was evaluated with the Short-Form Health Survey (SF-36). With respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 40 publications
(43 reference statements)
2
12
0
1
Order By: Relevance
“…While our scores for overall QoL and functional QoL were similar to those obtained for the general population, scores for PWB (22.4 [SD = 4.9] vs 25.1 [SD = 3.7]) and EWB subscales (20.7 [SD = 3.5] vs 21.2 [SD = 3.7]) in our study were significantly lower than in the general population . This pattern of results is consistent with other studies . Additionally, social QoL in our study was higher than levels found in the general population.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…While our scores for overall QoL and functional QoL were similar to those obtained for the general population, scores for PWB (22.4 [SD = 4.9] vs 25.1 [SD = 3.7]) and EWB subscales (20.7 [SD = 3.5] vs 21.2 [SD = 3.7]) in our study were significantly lower than in the general population . This pattern of results is consistent with other studies . Additionally, social QoL in our study was higher than levels found in the general population.…”
Section: Discussionsupporting
confidence: 88%
“…Sherman et al reported that physical functioning and energy were affected far more than the mental health functioning. The results also compare with Pulgar et al's study that reported diminished QoL outcomes on all subscales such as physical and emotional functioning although their sample consisted of mixed haematological cancer patients including myeloma, leukaemia and lymphoma who and were between <1 year and >2 years postdiagnosis. In another study of haematological patients approximately 5 years postdiagnosis, Molassiotis et al reported lower physical and social functioning but higher emotional functioning compared to healthy adults.…”
Section: Discussionsupporting
confidence: 55%
“…This difference may be explained partially by the fact that her sample of men was relatively small (n=34), her CES-D scores were considerably higher in both gender groups than ours, and she entered only two predictors into her regression models. Our group and many others have reported that higher depressive symptoms were associated with a lower QOL (Bower, 2008; Brown & Roose, 2011; Dodd et al, 2011; Dunn et al, 2011; Fann et al, 2008; Miaskowski et al, 2014; Osann et al, 2014; Pud, 2011; Pulgar, Alcala, & Reyes del Paso, 2013; Roland et al, 2013) and other adverse outcomes, including reduced adherence to treatment and other health behaviors (DiMatteo, Lepper, & Croghan, 2000) and increased perception of pain and other symptoms (Dunn et al, 2011; Fann et al, 2008; Gaston-Johanssen, Ohly, Fall-Dickson, Nanda, & Kennedy, 1999; Huang, Chen, Liang, & Miaskowski, 2014). Our findings reinforce the need for clinicians to assess for and treat depressive symptoms in cancer patients at the beginning RT.…”
Section: Discussionmentioning
confidence: 65%
“…Various reasons have been suggested for the experience of mental distress. In addition to the cancer itself as a source of mental stress in cancer patients, the symptoms burden of patients, fear of cancer recurrence, and even quality of life are also among the other contributions to stress [ 36 , 41 , 45 , 46 ]. It is the fact that patients who were suffering from cancers feel themselves having a need to cope with the challenge events.…”
Section: Discussionmentioning
confidence: 99%